The Effect of Welfare and Education Level on Personnel Performance in the Medical and Health Field of the West Java Regional Police - Pesiando Murajaya Dormitory; Enjang Sudarman; Sukiman Sukiman (Dinasti Publisher, 2026)
This study aims to determine and analyze the influence of welfare on personnel performance, the influence of education level on personnel performance, and the influence of both simultaneously on personnel performance in the Medical and Health Division (BIDOKKES) of the West Java Regional Police. The focus of this study is very relevant because the performance of BIDOKKES personnel is not only determined by technical competence, but is also influenced by the level of welfare and educational background of each personnel in carrying out police health service duties. The type of research used is quantitative research, namely research that utilizes numerical data to examine the relationship between variables objectively and measurably. In addition, this study is also supplemented with qualitative data, such as statements in questionnaires, consultation results, and short interviews with informants, to provide additional context regarding empirical conditions in the field. The population of this study consisted of 83 BIDOKKES personnel of the West Java Regional Police, and the entire population was used as respondents through a total sampling technique. Hypothesis testing was conducted using SPSS Version 29 software, which is capable of analyzing variable relationships with a high level of accuracy. The results showed that welfare (X1) and education level (X2) had a positive and significant effect on personnel performance (Y) partially. The R-Square value of 0.424, or 42.4%, indicates that personnel performance can be explained by these two variables, while the remaining 57.6% is influenced by other factors not examined. This finding opens up opportunities for further research to examine additional variables such as motivation, work experience, or work environment, to obtain a more comprehensive picture of the factors influencing BIDOKKES personnel performance